Latrunculin Analogues with Improved Biological Profiles by "Diverted Total Synthesis": Preparation, Evaluation, and Computational Analysis - Fürstner, Alois; Kirk, Douglas; Fenster, Michaël D. B.; Aïssa, Christophe; De Souza, Dominic; Nevado, Cristina; Tuttle, Tell; Thiel, Walter; Müller, Oliver (Chemistry : a European journal, 2007)
Deliberate digression from the blueprint of the total syntheses of latrunculin A (1) and latrunculin B (2) reported in the accompanying paper allowed for the preparation of a focused library of “latrunculin‐like” compounds, in which all characteristic structural elements of these macrolides were subject to pertinent molecular editing. Although all previously reported derivatives of 1 and 2 were essentially devoid of any actin‐binding capacity, the synthetic compounds presented herein remain fully functional. One of the designer molecules with a relaxed macrocyclic backbone, that is compound 44, even surpasses latrunculin B in its effect on actin while being much easier to prepare. This favorable result highlights the power of “diverted total synthesis” as compared to the much more widely practiced chemical modification of a given lead compound by conventional functional group interconversion. A computational study was carried out to rationalize the observed effects. The analysis of the structure of the binding site occupied by the individual ligands on the G‐actin host shows that latrunculin A and 44 both have similar hydrogen‐bond network strengths and present similar ligand distortion. In contrast, the H‐bond network is weaker for latrunculin B and the distortion of the ligand from its optimum geometry is larger. From this, one may expect that the binding ability follows the order 1 ≥ 44 > 2, which is in accord with the experimental data. Furthermore, the biological results provide detailed insights into structure/activity relationships characteristic for the latrunculin family. Thus, it is demonstrated that the highly conserved thiazolidinone ring of the natural products can be replaced by an oxazolidinone moiety, and that inversion of the configuration at C16 (latrunculin B numbering) is also well accommodated. From a purely chemical perspective, this study attests to the maturity of ring‐closing alkyne metathesis (RCAM) catalyzed by a molybdenum alkylidyne complex generated in situ, which constitutes a valuable tool for advanced organic synthesis and natural product chemistry. The power of “diverted total synthesis”, that is, the de novo synthesis of “natural product like” structures, is illustrated by a concise approach to a focused library of latrunculin analogues. The best compounds of this series surpass the activity of the naturally occurring macrolide latrunculin B (see figure) in their effect on the actin cytoskeleton. A computational analysis of the bonding situation in the binding site of the protein allows us to rationalize these experimental results.